Analisis Brand Equity dan Customer Loyality Celebrity Fitness Cabang Mall Puri Indah Jakarta Barat - Robertus Tang Herman; Ryandhi Wijaya (Bina Nusantara University, 2010)
This study aims to determine the condition of the elements of brand equity Celebrity Fitness, namely knowing the brand awareness, brand association is formed, to know how the perception of performance and the interests of the brand, how consumers' brand loyalty, and what attributes of service quality a priority for improved performance to can meet consumers' desire to achieve satisfaction. The method used is descriptive method with the sampling technique using probability sampling (simple random sampling), with regional research area in West Jakarta. The results of this study indicate that the overall brand equity of the company is good enough to position the brand awareness top of mind, the brand associations that are formed from Celebrity Fitness is where fitness is comfortable and fun and has a diverse and interesting program, another association was formed team aggressive promotion. Performance level of perceived quality is also good enough. To Brand loyalty are in poor condition because of the high percentage of switchers. Overall customer satisfaction levels are good enough just need a little improvement in the performance of staff. The implication of this research is PT Exertainment should improve the performance of some quality attributes are prioritized so that the loyalty of the members has also increased.